2020
DOI: 10.48550/arxiv.2004.00334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large dispersive interaction between a CMOS double quantum dot and microwave photons

David J. Ibberson,
Theodor Lundberg,
James A. Haigh
et al.

Abstract: We report a large coupling rate, g0/(2π) = 183 MHz, between the charge state of a double quantum dot in a CMOS split-gate silicon nanowire transistor and microwave photons in a lumpedelement resonator formed by hybrid integration with a superconducting inductor. We enhance the coupling by exploiting the large interdot lever arm of an asymmetric split-gate device, α = 0.72, and by inductively coupling to the resonator to increase its impedance, Zr = 560 Ω. In the dispersive regime, the large coupling strength a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The magnitude of the signal increases quadratically with the gate lever arm to the sensor dot [28]. Based on the values in our device (α sensor = 0.24 and α qubit = 0.47) and similar asymmetries reported for nominally identical devices [31,51], SNR power could be increased by 16× simply by swapping the assignment of sensor and qubit.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The magnitude of the signal increases quadratically with the gate lever arm to the sensor dot [28]. Based on the values in our device (α sensor = 0.24 and α qubit = 0.47) and similar asymmetries reported for nominally identical devices [31,51], SNR power could be increased by 16× simply by swapping the assignment of sensor and qubit.…”
Section: Discussionsupporting
confidence: 62%
“…Further improvements in SNR power (∼20× and ∼16× respectively) can be expected by further optimising the resonator design to detect capacitance changes [51] and by lowering the noise floor through use of a quantum-limited amplifier [33]. Combining these methods, improvements in SNR power of three orders of magnitude are possible, bringing single-shot readout well within reach while simultaneously reducing the RF power used for readout to avoid limiting the minimum measurable Zeeman splitting.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have provided a detailed explanation and a method to engineer these low charge decoherence values by easily modifying the contribution of the interdot capacitance C m to the total QD capacitance, which we can easily assess and tune by exploring the DQD charge stability diagram. Furthermore, this experiment sheds new light on the puzzling observation reported by different experiments on QD-resonator hybrid system [23,42] which observed that g and Γ 2 can vary considerably within the same device configured in different regions of the DQD charge stability diagrams.…”
Section: Discussionmentioning
confidence: 58%
“…Spin-based quantum computing based on silicon quantum dots is rapidly evolving [1], motivated in part by the prospect of scalable foundry fabrication that so far allowed coherent control of hole spins [2,3] and electricallydriven electron spin resonance [4]. Foundry-fabricated nanowire devices controlled by split-pair side gates recently allowed various spin-relaxation experiments [5,6] and charge-sensing functionalities [7][8][9][10]. However, scaling from few-qubit circuits towards fault-tolerant quantum processors will likely involve dense two-dimensional arrays of singly-occupied quantum dots [11,12].…”
Section: Introductionmentioning
confidence: 99%